ANALISIS HARGA, VOLUME PERDAGANGAN, DAN RETURN SAHAM SEBELUM DAN SESUDAH INFORMASI AKUISISI PADA PT. XL AXIATA Tbk. dan PT. AGUNG PODOMORO LAND Tbk. - Tasa Ushuaia; Bulan Prabawani (Universitas Diponegoro, 2016)
Economic developmentrequires company to work better and be able to survive from anintense competition between companies. In modern era, telecommunication and propertyindustries are the mostdeveloped industry. In maintaining the continuity of business, there areseveral strategies that can beundertakenby company, one of which is the incorporation of abusiness entity such as an acquisition.The purpose of this research is to find differentiation among stock price, stock tradingvolume and stock return before and after acquisition on the telecommunication and propertyindustry, acquisition of PT. XL Axiata Tbk. with Axis Telekom Indonesia and acquisition betweenPT. Agung Podomoro Land Tbk. and PT. Graha Cipta Karisma.The results show a significant difference to stock price before and after acquisitioninformation of PT. XL Axiata Tbk. and PT. Agung Podomoro Land Tbk., but no significantdifference on trading volume and stock return (indicated by abnormal return to see informationcontent from that event). Based on these results it can be concluded that investor opinion on theacquisition information is normal so the trading volume and stock return are not changesignificantly. The significant difference of stock price may be due to investors's views about theacquisition and its accordance with the theory saying that acquisition can improve companiesperformance.